The Cusum Test with Ols Residuals - Ploberger, Werner; Kramer, Walter (Econometrica, 1992)
The authors show that the CUSUM test of the stability over time of the coefficients of a linear regression model, which is usually based on recursive residuals, can also be applied to ordinary least squares residuals. The authors derive the limiting null distribution of the resulting test and compare its local power to that of the standard procedure. It turns out that neither version is uniformly superior to the other. Copyright 1992 by The Econometric Society.